Mexico : Report on the Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report ;, 2013)
This Report on the Observance of Standards and Codes (ROSC) Data Module provides an assessment of Mexico's macroeconomic statistics against the Special Data Dissemination Standard (SDDS) complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework (DQAF) 2012. Mexico's Consumer Price Index (CPI) and Producer Price Index (PPI) have solid institutional, conceptual and methodological, and source data foundations achieved through implementation of international best practices. Implementation of good practice extends to the serviceability and dissemination aspects of both indexes. It is also observed that CPI and PPI both benefit from the application of sound practices in concepts and methods.